Analysis of information system success model on e-sambat in reporting service complaints in Pasuruan city - Pierre Agara Pratama; Tree Setiawan Pamungkas; Hermanto Rohman (Institute of Computer Science (IOCS), 2024)
The development of the times has also taken a place, especially in the implementation of public services in the community, one of the related programs is the existence of an application called E-Sambat, where this application is a digital platform that can be used by the people of Pasuruan City as a form of brave complaint. Researchers found several interesting things, including that most of the random sources the researchers met did not know them and instead asked about the complaint reporting application, there were differences in the E-Sambat menu features when accessed via the application and browser. This led researchers to conduct research on analysis of satisfaction factors using the E-Sambat application in reporting service complaints in Pasuruan City. This research uses the D&M IS Success Update Success Model theory which was updated in 2003 by Delone and McLean. Meanwhile, measuring the success of the E-Sambat application is by using the DeLone and McLean information system success model. In this success model, system quality, information quality, and service quality are tested and their impact on user satisfaction